The Effect of Electroplating Hard Chrome with Different Dissolvent Compositions to the Mechanical Properties of ST-37 - Mohammad Jufri; Yeshar Ego Ginola; Rr. Heni Hendaryati; Ali Saifullah; Daryono (JEMMME (Journal of Energy, Mechanical, Material, and Manufacturing Engineering), 2021)
Electroplating hard chrome is a metal plating process with hard chrome which aims to not only coat as decorative, but also to coat metal surfaces more strongly, according to their use in the engineering world. In addition to decorative properties, the advantages of surface treatment techniques can also increase hardness, wear resistance, and corrosion resistance. The purpose of this research is generally to determine the effect of different solution compositions in the electroplating process of hard chrome on the impact strength of the structure on ST-37 steel. This time the specimens are 100mm x 6mm x 6mm and 50mm x 50mm as many as 3 pieces. In this study, the electroplating process of hard chrome was carried out using different parameters of the CrO3 solution composition from previous studies, namely 200 gr/lt, 350 gr/lt, and 400 gr/lt with an immersion time of 22 minutes. The results of this electroplating process were tested by testing the impact strength and microstructure. The results of the study can be concluded that the more the composition of the solution, the higher the impact toughness. The highest impact toughness value is 0.998 joules/mm2 at a solution concentration of 400 grams/litre and the surface results on ST-37 steel after getting hard chrome electroplating treatment is that the surface has Cr elements attached and gets thicker with increasing concentration which is used as a variation with the same immersion time.